Association between newly developed body indices and body mass index in young adults in a Nepali setting: a cross-sectional study - Aryal, Vibina; Bhusal, Pujan; Ghimire, Dayaram; Majumder, Anirban (Journal of Chitwan Medical College, 2025)
Introduction: New indices to predict adiposity, including ‘a body shape index’ (ABSI), and the ‘body roundness index’ (BRI) for assessment of adiposity and health risk. This study aims to explore the association between already in use ‘body mass index‘ (BMI) and these new indices to enhance obesity assessment and risk stratification. Method: An observational cross-sectional study was done among 150 medical and dental students at National Medical College, Birgunj from 01 Nov 2021 to 30 Mar 2022. Ethical clearance was taken from the Institutional Review Committee. Simple random sampling was applied. Waist circumference (WC) was measured in cm. The BMI, ABSI and BRI were calculated. Correlation between different parameters was determined. Result: Out of 150 participants, a very high positive correlation was observed between WC and BRI in males (r=0.919, p<0.001) and in the total population (r=0.875, p<0.001). In females, a very high positive correlation was found between WC and ABSI (r=0.935, p<0.001). Negative correlations were seen between BMI and ABSI in both males (r=-0.166) and females (r=-0.106), as well as in the total population (r=-0.071). Conclusion: Study showed a strong positive correlation between BMI and BRI. Also, WC correlated strongly with BRI and ABSI; highlighting the potential utility of BRI and ABSI as complementary tools alongside BMI for more accurate assessment of obesity an health risks in the Nepali young population.